2012
DOI: 10.1021/ac301612n
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Ionic Mobility Filter for Depletion Zone Isotachophoresis

Abstract: We present a novel concept of filtering based on depletion zone isotachophoresis (dzITP). In the micro/nanofluidic filter, compounds are separated according to isotachophoretic principles and simultaneously released selectively along a nanochannel-induced depletion zone. Thus, a tunable low-pass ionic mobility filter is realized. We demonstrate quantitative control of the release of fluorescent compounds through the filter using current and voltage actuation. Two modes of operation are presented. In continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Since then a vast amount of research has been performed in ion concentration polarization (ICP) and ICPF. 5,17,[21][22][23][24][25][26][27][28][29][30] We refer the reader to a short theoretical background of ICPF in the ESI † in order to define the requirements of the droplet generator. For a deeper theoretical background of ICPF the reader is referred to our previous work 1 or the work of Ouyang et al 31 and the more recent work of Gong et al 6,7 There are two operating modes in ICPF namely peak and plateau mode.…”
Section: Ion Concentration Polarization Focusingmentioning
confidence: 99%
“…Since then a vast amount of research has been performed in ion concentration polarization (ICP) and ICPF. 5,17,[21][22][23][24][25][26][27][28][29][30] We refer the reader to a short theoretical background of ICPF in the ESI † in order to define the requirements of the droplet generator. For a deeper theoretical background of ICPF the reader is referred to our previous work 1 or the work of Ouyang et al 31 and the more recent work of Gong et al 6,7 There are two operating modes in ICPF namely peak and plateau mode.…”
Section: Ion Concentration Polarization Focusingmentioning
confidence: 99%
“…Such a compound is usually named electrophoretic spacer which has been previously reported in ICPF. 3,40…”
Section: Krfmentioning
confidence: 99%
“…Since its introduction vast amount of research has been performed with this technique, where Quist et al 2 demonstrated that apart from concentration also separation occurred. [3][4][5][6][7]34 Though the technique offers a very powerful and simple analytical tool, a disadvantage is that the focused and separated analytes are "trapped" inside the chip in picoliter volumes. Further analysis, for example by mass spectrometry, thus is impossible.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous review, the introduction of depletion zone ITP (dzITP) by Quist et al was highlighted as an interesting approach to sample treatment because it leverages CF gradient focusing to create a depletion zone using only a single electrolyte. Since then, the authors used this approach with a novel filtering principle in combination with dzITP . The filtering method is based on the balance of fluxes such that selectivity can be obtained as the dzITP orders compounds into distinct zones before they pass the depletion zone.…”
Section: Stackingmentioning
confidence: 99%